The Determinant Of Students Entrepreneurial Interest - Puspasari, Elsa; Rizani, Asri; Anggraeni, Oki; Nasori, Ahmad; Astarani Aslindar, Dwi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2024)
Phenomenon/Issue: One of the critical challenges in Indonesia is the high unemployment rate, which necessitates promoting entrepreneurship as a solution to create employment opportunities and drive innovation. Purpose: This study aims to analyze and identify the factors influencing students' entrepreneurial interests, focusing on the roles of entrepreneurial knowledge and motivation. Novelty: The novelty of the study lies in quantifying the relationship between entrepreneurial interest and factors such as entrepreneurial knowledge and motivation, providing insights into their partial contributions to students’ entrepreneurial aspirations. Research Methods: The study employs a quantitative approach with a sample of 39 students selected through proportional random sampling. Data collection was conducted using questionnaires, and the analysis was performed using descriptive statistical methods. Results: The findings reveal a 55.9% relationship between entrepreneurial interest and entrepreneurial knowledge. Additionally, entrepreneurial motivation contributes 16.4% to entrepreneurial interest. These results indicate that both entrepreneurial motivation and knowledge partially influence students' entrepreneurial aspirations. Research Contributions: This study contributes to the understanding of how entrepreneurial education impacts students' entrepreneurial interests. It emphasizes the importance of campuses and governments allocating more resources and time to entrepreneurship education to nurture and enhance students' entrepreneurial capabilities, thereby addressing the unemployment issue in Indonesia.